Dilematik Kontrasepsi pada Wanita Usia Subur Antara Jenis, Lama Penggunaan dan Berat Badan - Eka Atik Ismawati; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Contraception is an effort to prevent pregnancy. Contraception consists of hormonal and non-hormonal contraception. Hormonal contraception is one of the contraceptives that is very popular with the respondents, because of its practical use, work effectively,can be used immediately after the postpartum period, and its affordable and safe. In addition to having advantages, all contraceptives also have weaknesses or side effects in a certain period of time, including weight gain. The design of this study uses a quantitative research type using an analytical survey through a cross-sectional approach. The number of respondents was 66 people using purposive sampling. The test used was the contingency coefficient. The results of the contingency coefficient test showed that there was a relationship between the use of types of contraception and changes in body weight with a p value of 0.020 while the relationship between the duration of contraception use and changes in body weight had a p value of 0.008.